An Assessment of Water Resources Management using The WEAP Model in The Gamasyab Watershed, The Province of Kermanshah, Iran - Ata Amini; Mitra Javan; Afshin Eghbalzadeh; Mohamadrahim Ghasemi (مهندسی منابع آب, 2017)
The water demand is rapidly increasing due to economic and social development and population growth. In keeping with the freshwater restrictions, the allocation of water needs to take a comprehensive view and integrated management approaches are vital in different sectors. This study was implemented in the Gamasyab Watershed, which is the main sub-watershed of the Karkheh River. Much of the watershed is located in the Province of Kermanshah, while its headwaters are in the Province of Hamadan. In this study, the WEAP Software was used as a powerful tool to assess an integrated water resources management for investigating an applied management in the Gamasyab Watershed, and evaluating the effect of upstream dams on the performance of the Bistoon reservoir. Long term hydrological data were used to model the water resources and demands in the watershed. The water demands were obtained using the data of population, agriculture, and industries, and the environmental flow requirements determined using the Montana Method. Different management scenarios were defined in accordance with the current conditions and watershed development perspective. The results indicated that the demands maybe fully met under the present conditions; however, the demands will exceed the available water in the Bistoon Reservoir if the planned dams come in to operation. Its regards to the importance of considering the principles of integrated water resources management, the results of this study may be used with certainty by the researchers and decision-makers in the water sector in Iran.